Reactivities of vinyl azides and their recent applications in nitrogen heterocycle synthesis. Issue 13 (3rd March 2015) - Hu, Bao; DiMagno, Stephen G.
Abstract : This review categorizes the active intermediates generated from denitrogenation of vinyl azides under different reaction conditions, and highlights newly discovered transformations of vinyl azides that lead to convenient syntheses of N-heterocycles. Abstract : Nitrogen heterocycles are abundant in natural products and pharmaceuticals. An emerging interest among synthetic chemists is to apply vinyl azides as a pivotal three-atom synthon for the construction of structurally complex and diverse N-heterocyclic skeletons. The unique features of the azide group connected to an alkene moiety permit vinyl azides to function as electrophiles, nucleophiles, or radical acceptors; their access to diverse reaction pathways provides great opportunities to generate highly reactive intermediates with often unusual or unconventional reactivities. This tutorial review will systematically illustrate the reactivities of vinyl azides and describe recent breakthroughs in the development of new transformations that create N-heterocycles.